Territorialidades da modernização da agricultura em Vicente Dutra - RS entre os anos de 1966 e 1980 - Spier, Gilberto (2010)
Brazilian agriculture has been going, in the last decades, through deep transformations conducted by a process of modernization, idealized aiming at integrating, systematically, industry and agricultural activities, through modern technologies. The main argument to implement modern technology was to reduce the famine in the planet. Therefore, thousands of Brazilian peasants were affected by such transformations. Some of them changed their way and were assimilated; others, were sent away from the rural area, while others still resist to the agricultural modernization process. The main verified changes were: the physical energy was being substituted by mechanic energy, where motorized equipment were present; in the genetic field, the seeds and hybrid races substituted the common or creole ones and, in chemistry, the intensive use of synthetic fertilizers and poisons altered the relation between the farmer and the environment. In Vicente Dutra- RS, small municipality, situated at northwest region of Rio Grande do Sul State, started having agricultural modernization around 1960. Among the main consequences it could be highlighted the rural deterritorialization, where hundreds of families were deterritorialized from the field activity, the great majority moving to cities searching for a place to live and work, decreasing, consequently, the local community in absolute number. Although many transformations occurred, many peasants continue to develop an agriculture of resistance to the agricultural modern process and they keep important links to field agriculture. In the field can be noticed significant changes, such as: alterations to traditional alimentation; solidarity gave room to individuality; soil was degraded, increasing the cost of production; streams and rivers were poisoned, and the commercial land dominated the landscape. The rural territory of Vicente Dutra-RS shows, in its great part, the faces of agricultural modernization. Even though, it is possible to identify some forms of reaction to the thought of agricultural modernization, such as: the growing of traditional subsistence; cooperativism, and initiatives of transformation of production to direct sale to the final consumer. Therefore, the agricultural modernization installed in Vicente Dutra-RS is partial, and the peasants keep, even with certain difficulty, their traditional uses and customs.